2017
DOI: 10.1177/1533317517703477
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Programs May Be Especially Engaging for Aged Care Residents With Cognitive Impairment: Findings From the Avondale Intergenerational Design Challenge

Abstract: Intergenerational programs are an authentic way to engage elders in meaningful activity and report benefits to both elders and youth. The Avondale Intergenerational Design Challenge (AVID) randomly assigned small teams of technology students aged 13 to 15 years (total N = 59) to 1 of 24 aged care residents with a range of cognitive impairment. Students met with the resident 4 times over 15 weeks and ultimately crafted a personalized item for them. Students showed no change in self-reported attitudes to elders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(43 citation statements)
references
References 36 publications
0
42
0
1
Order By: Relevance
“…Additionally, students mentioned finding it hard to balance providing assistance and allowing the older participants the opportunity to be independent (Lokon et al, 2012). Additionally, Baker et al (2017) found no significant benefits for students regarding attitudes or empathy towads the older adults. The authors suggested that the relatively short amount of face-to-face time between both generations could have been insufficient for the intergenerational dementia program to have an effect on students' attitudes and levels of empathy (Baker et al, 2017).…”
Section: Relationship Building Between the Different Generationsmentioning
confidence: 94%
See 4 more Smart Citations
“…Additionally, students mentioned finding it hard to balance providing assistance and allowing the older participants the opportunity to be independent (Lokon et al, 2012). Additionally, Baker et al (2017) found no significant benefits for students regarding attitudes or empathy towads the older adults. The authors suggested that the relatively short amount of face-to-face time between both generations could have been insufficient for the intergenerational dementia program to have an effect on students' attitudes and levels of empathy (Baker et al, 2017).…”
Section: Relationship Building Between the Different Generationsmentioning
confidence: 94%
“…In programs that had a buddy system, participants were linked to each other one-on-one or were put in consistent small groups. The main positive outcome associated with the buddy system was the creation of strong relationships within each group (Alant, Geyer, & Verde, 2015;Baker et al, 2017;Camp et al, 1997;Camp, Orsulic-Jeras, Lee, & Judge, 2004;Chung, 2009;Guerrero, Jimenez, & Tan, 2017;Harris & Caporella, 2014, 2018Isaki & Harmon, 2015;Lee, Camp, & Malone, 2007;Lokon et al, 2012Lokon et al, , 2017Low, Russell, McDonald, & Kauffman, 2015). However, Low et al (2015) reported that it was not always possible to group the same participants due to absences.…”
Section: Buddy Systemsmentioning
confidence: 99%
See 3 more Smart Citations